Penggunaan Metode AHP dan Topsis dalam Pemilihan Penyedia Suku Cadang Instalasi Perawatan Sarana Rumah Sakit - Wahid Al Jufri; Agung Triayudi; Ben Rahman (Universitas Budi Darma, 2022)
Determination in choosing a supplier is one of the strategic programs and needs to be more objective, often the decision making in choosing a supplier is only based on intuition, habit and experience, until now there is no mechanism or method for this that is suitable or only according to universal select criteria. Hospital Facility Maintenance Facility (IPSRS) is a facility that oversees all maintenance and repair work on non-medical facilities at the National Brain Center Hospital, including building maintenance, electrical systems, plumbing, AC management, surveillance camera or CCTV maintenance, and motor generator repair. and telephone control generator. To select the expected spare parts supplier, it is necessary to apply the SPK Ideal Solution Similarity Order Preference Technique (TOPSIS) method and combine it with the Analytical Hierarchy Process (AHP) method to facilitate the process of selecting more than one alternative. The criteria determined in this study are S1 with Price, S2 with Quality, S3 with Speed and S4 with Completeness. With these criteria, it can be used as material to determine the Decision Support carried out by the system. In the results of this study the determination of the criteria using AHP with the results of the Consistency Ratio value of 0.004 which means if the value is above 0.01 then the results are declared consistent. As well as for the design using the Topsis method, the positive ideal solution on the criteria S1 is worth 0.13282, S2 is worth 0.07954, S3 is 0.04085 and S4 is 0.0422. Meanwhile, for the negative ideal solution, S1 is worth 0.04981, S2 is 0.02983, S3 is 0.02043 and S4 is 0.0211. The first rank is P7 with a value of 0.813 and the last order is P8 with a value of 0.13. So, from the results of the assessment carried out by the system based on the weight value for ranking using the TOPSIS method which occupies the top three positions, PT. Cipta Karya Teknik with a total of 0.813 or 81.3%, followed by PT. Karya Mandiri Indonesia with a total of 0.802 or 80.2%, and PT. Indah Harapan Nusa with a total of 0.796 or 79.6%. As for the bottom three positions are PT. Tunggal Teknik Indo with a total of 0.292 or 29.2%, then PT.Harapan Maju Bersama which has a total of 0.139 or 13.9% and the last one is PT. Forward Rise Simultaneously with a value of 0.130 or 13%.